Soil compaction during harvest operations in five tropical soils with different textures under eucalyptus forests - Martins, Paula Cristina Caruana (2018)
Traffic of farm machinery during harvest and logging operations has been identified as the main source of soil structure degradation in forestry activity. Soil susceptibility to compaction and the amount of compaction caused by each forest harvest operation differs according to a number of factors (such as soil strength, soil texture, kind of equipment, traffic intensity, among many others), what requires the adequate assessment of soil compaction under different traffic conditions. The objectives of this study were to determine the susceptibility to compaction of five soil classes with different textures under eucalyptus forests based on their load bearing capacity models; and to determine, from these models and the precompression stresses obtained after harvest operations, the effect of traffic intensity with different equipment in the occurrence of soil compaction. Undisturbed soil samples were collected before and after harvest operations, being then subjected to uniaxial compression tests to determine their precompression stress. The coarse-textured soils were less resistant and endured greater soil compaction. In the clayey LVd2, traffic intensity below four Forwarder passes limited compaction to a third of the samples, whereas in the sandy loam PVd all samples from the 0-3 cm layer were compacted regardless of traffic intensity. The Feller Buncher and the Clambunk presented a high potential to cause soil compaction even with only one or two passes. The use of soil load bearing capacity models and precompression stress determined after harvest and logging operations allowed insight into the soil compaction process in forestry soils.